Determination of amphetamine, methamphetamine and dimethamphetamine in human urine by solid-phase microextraction (SPME) gas chromatography mass spectrometry - Myung, SW; Min, HK; Kim, S; Kim, M; Cho, JB; Kim, TJ (ELSEVIER SCIENCE BV, 1998)
A simple and rapid assay method for three stimulant drugs (amphetamine, methamphetamine, and dimethamphetamine) in human urine using solid-phase microextraction was developed. In solid-phase microextraction, the drugs were equilibrated between the adsorbent coated-fiber and aqueous sample matrix. After adsorption of the analytes, the fiber was directly transferred to the injector of a gas chromatograph, where the analytes were thermally desorbed and subsequently separated by the gas chromatograph and detected by mass spectrometer. The solid-phase microextraction method, which did not require solvents, was found to be a fast and simple analytical method. We optimized the solid-phase microextraction technique, for factors such as the NaCl salt effect (30%), pH effect (pH=12.4), equilibration time (30 min), desorption time (1 min) and coated-fiber type (100 mu m poly(dimethylsiloxane)) and detected the stimulants in human urine, obtained from human subjects. The detection limits of each drug were below 1-10 ng/ml. The developed method can be applied to the abused drug test. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: SINGLE-COLUMN PROCEDURE; BOND ELUT CERTIFY; PLASMA; DRUGS; BLOOD